Left-ventricular hypertrophy associates to impaired maximal mycardial perfusion in endurance-trained men - Laaksonen, M. S.; Heinonen, I.; Luottolahti, M.; Nuutila, P.; Raitakari, O.; Knuuti, J.; Kalliokoski, K. K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Long-term endurance training induces morphological adaptations in heart, such as left-ventricular (LV) hypertrophy caused by wall thickening and cavity enlargement. Interestingly, these anatomical changes in the heart are strikingly similar to certain pathophysiological changes (Pellicia 2000). Previous studies have shown that the perfusion response in myocardium during dipyridamole- or adenosine infusion is decreased in several pathophysiological states with LV hypertrophy (e.g. Stolen et al. 2004). However, studies in endurance athletes with LV hypertrophy have shown contradictory results on myocardial perfusion response ranging from reduced to increased myocardial perfusion during dipyridamole- or adenosine-induced vasodilation compared to untrained men (Kjaer et al. 2005; Kalliokoski et al. 2002). The degree of hypertrophy could explain the discrepant findings in studies in athletes, but it has not been thoroughly investigated. Thus, we examined totally 31 endurance athletes (ET) and 25 untrained (UT) men in order to study the association between myocardial functional and anatomical parameters measured with echocardiography, and myocardial perfusion (at rest and during maximal vasodilation induced by iv adenosine) measured with Positron Emission Tomography. Both VO2max (60+-5 vs 42+-8 ml/kg/min, p<0.001) and LVmass index (169+-27 vs 102+-15 g/m2, p<0.001) were markedly higher in ET. Resting myocardial perfusion was similar between the groups (ET 0.7+-0.2 vs UT 0.8+-0.2 ml/g/min, p=0.22) whereas adenosine-stimulated perfusion was lower in ET (2.9+-1.0 vs 3.7+-1.0 ml/g/min, p<0.01). VO2max correlated inversely with adenosine-stimulated perfusion in ET (r=-0.39, p=0.03) and with resting perfusion in UT (-0.49, p=0.01). Forward LV work correlated linearly with resting perfusion in both groups (ET r=0.54, p<0.01; UT r=0.50, p=0.01). ET group was further divided into three subgroups according to LVmass index (ET1: LVmass index <150g/m2, n=9; ET2 LVmass index 150-180 g/m2, n=12; ET3 LVmass index >180 gm2, n=10). Adenosine-induced myocardial perfusion decreased gradually when LVmass increased (UT 3.7+-1.+0 vs ET1 3.3+-0.9 vs ET2 2.7+-1.4 vs ET3 2.6+-0.5 mL g-1 min-1, p=0.008). LVmass index was also inversely related to adenosine-induced perfusion in entire study population (r=-0.46, p<0.01). Therefore, these results suggest that endurance training-induced severe cardiac hypertrophy impairs myocardial perfusion capacity.